Self-crosslinking rubber/rubber and rubber/thermoplastic blends: a review (2001 Reviews) - Antony Prince; De S K; van Duin Martin (Rubber Chemistry and Technology, 2001)
Blends of two or more polymers having appropriate reactive groups can be crosslinked through condensation or substitution reactions in the absence of crosslinking chemicals when molded at high temperatures for prolonged times. When at least one of the two polymers is a rubber, such blends are called self-crosslinking rubber blends. Self-crosslinking rubber/rubber blends included in this review are binary CSM/ENR, ENR/XNBR, CR/ENR, ENR/Zn-SEPDM, CSM/XNBR and CR/XNBR blends, and ternary CR/XNBR/ENR and CSM/XNBR?ENR blends. Self-crosslinking thermoplastic/rubber blends include binary PVC/XNBR, PVC/ENR, PVC/NBR, PVC/HNBR, PAA/CR and PAA/ENR blends, and a ternary PVC/ENR/XNBR blend. The formation of crosslinks in self-crosslinking blends is manifested in the rise of the rheometer torque with time. Solvent swelling studies and dynamic mechanical analysis support the self-crosslinking behavior of the blends. The extent of crosslinking depends on the amount and reactivity of the functional groups of the two blend components, the time and temperature of the reaction. In general, the self-crosslinked rubber/rubber blends behave like conventional rubber vulcanizates with respect to physical properties and can be reinforced by fillers. Infrared spectroscopy has been used to identify the chemical structures formed during self-crosslinking, allowing the elucidation of the mechanism of self-crosslinking.
Keywords: Rubber/Rubber blends; Rubber/thermoplastic blends